2009
DOI: 10.1115/1.3072489
|View full text |Cite
|
Sign up to set email alerts
|

Aerothermal Performance of Streamwise and Compound Angled Pulsating Film Cooling Jets

Abstract: The quantification of aerothermal loss is carried out for streamwise and compound angled film cooling jets with and without large scale pulsation. This paper reports on the simultaneous measurements of the unsteady pressure and temperature field of streamwise and a 60 deg compound angled film cooling jet, both with a 30 deg surface angle over a flat plate with no pressure gradients. Turbine representative nondimensionals in terms of the geometry and operating conditions are studied. The main flow is heated mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The heat transfer coefficient was normalized by the value of the turbulence heat transfer coefficient on flat plate of x/d=0 calculated by Eq. (14).…”
Section: Results and Discussion 41 Film Cooling Effectiveness And Heamentioning
confidence: 99%
See 1 more Smart Citation
“…The heat transfer coefficient was normalized by the value of the turbulence heat transfer coefficient on flat plate of x/d=0 calculated by Eq. (14).…”
Section: Results and Discussion 41 Film Cooling Effectiveness And Heamentioning
confidence: 99%
“…(12) . In order to evaluate the aerodynamic loss generated from cooling holes, the approach of Aga et al [14] was used and reference pressure P t,ref was defined.…”
Section: Aerodynamic Investigations 241 Total Pressure Loss Measurementioning
confidence: 99%
“…The mixing losses caused by the film cooling can be divided into aerodynamic loss and aerothermal loss, as described in [22,23]. Although the entropy generation is not considered for the mixing of the mainstream flow and the coolant flow, the aerodynamic loss is customarily used as an evaluation criterion, which is also the selection in present study.…”
Section: Data Reductionmentioning
confidence: 99%
“…Traditionally, the total pressure loss coefficient is used to indicate the aerodynamic loss. Assuming the mainstream flow and the coolant flow is mixed ideally, the total pressure of the mixing flow p t,mix can be calculated as follow [22] where m c and m m are the mass flow rates of the coolant and the mainstream hot gas, respectively, p t,cin and p t,m are the…”
Section: Data Reductionmentioning
confidence: 99%
“…The results of Aga et al 9 showed that the pulsating jet had greater thermal mixing and changed the size of the jet. Due to the greater penetrating power near the hole and the effective blowing ratio change, the entropy loss of the jet pulsating along the flow was twice as large as the entropy loss of the stable jet.…”
Section: Introductionmentioning
confidence: 99%